Digitalization of educational organizations as a product- and process-innovation in the data economy: managerial and methodological aspects - A. I. Shinkevich; E. Sh. Shaimieva; G. I. Gumerova (Russian Journal of Economics and Law)
Objective: to reveal the essence of educational organizations’ digitalization as the implementation of product- and processinnovations in their innovation activity from the managerial viewpoint, including (here) innovation statistics in the data economy. The research tasks were: to formulate the essence of educational organizations’ digitalization as product- and process-innovations in their innovation activity in the digital economy based on the analysis of scientific works; to identify product- and process-innovations as a result of educational organizations’ digitalization; to form tools of educational organizations’ digitalization in the context of product- and process-innovations in the form of methodological material.Methods: analysis, synthesis, classification. The study object is the processes of educational organizations’ digitalization as an integral part of their innovative activity under the fourth industrial revolution. The study subject matter is product- and process-innovations implemented in the process of educational organizations’ digitalization.Results: the paper identifies product- and process-innovations as a result of educational organizations’ digitalization, compiles a list of them, while taking into account the processes of virtualization of assets, management and platformization in the internal and external environments of an educational organization. The concept of “digitalization of educational organizations” was clarified: it is a set of processes of virtualization and platformization, considered as an integral part of the innovative activity of educational organizations, which results in product- and process-innovations. Recommendations for experts in the field of educational organizations’ digitalization were developed, in terms of normative and legal regulation of the process under study, its organization, methodological support and achievement of the educational system’s technological sovereignty based on the introduction of product- and process-innovations.Scientific novelty: consists in revealing the essence of an educational organization’s digitalization as part of its innovative activity, while distinguishing the product- and process-innovations in theoretical and practical virtualization and platformization of the issue.Practical significance: the study results can be used to form strategies for managing product- and process-innovations arising during digitalization of educational organizations and to collect statistical information on the innovation activity of educational organizations in the digital economy.